The Perception of a Three-Dimensional-Printed Heart Model from the Perspective of Different Stakeholders: A Complex Case of Truncus Arteriosus - Biglino, Giovanni; Moharem-Elgamal, Sarah; Lee, Matthew; Tulloh, Robert; Caputo, Massimo (Frontiers in Pediatrics, 2017)
The case of an 11-year-old male patient with truncus arteriosus is presented. The patient has a right aortic arch, a repaired truncus arteriosus, pulmonary artery stenosis as well as conduit stenosis, with a complex surgical plan being discussed. In order to gather additional insight into the patient’s anatomy prior to the surgery and to facilitate communication with the patient’s parents, a three-dimensional (3D) model of his heart and main vessels was created from computed tomography (CT) data. Feedback was collected from different stakeholders. The patient and his parents were both struck by the size of the heart, with the parents further elaborating on how the 3D model was more intuitive a tool than medical images as well as “an helpful talking point to the other members of the family” and potentially also at school. The surgeon and cardiologist commented on gaining better understanding of the 3D relationship between a markedly narrowed right pulmonary artery and the aorta, with the surgeon ultimately coming to a decision of dividing the ascending aorta quite high to access the right pulmonary artery for patch reconstruction and thus planning to arrest the circulation beforehand. The imaging expert remarked on the potential to “improve communication in multidisciplinary meetings”, whilst a medical trainee, who also had a chance to evaluate the model, remarked that “having the model in front of me and being able to see the exact abnormality makes this particular case much more memorable. […] 3D printed models could have immense potential in pathology and anatomy teaching for the training of healthcare professionals”.